PENTINGNYA ETIKA KRISTEN DALAM PENDIDIKAN AGAMA KRISTEN TERHADAP ANAK SEKOLAH MINGGU SEBAGAI DASAR PEMBENTUKAN KARAKTER - Yuli Ferianti (STAK Anak Bangsa, 2021)
AbstractThis article contains the important role of ethics in teaching Christian Religious Education to Sunday School children. This is due to the lack of good attitudes that occur in children of the current generation, indicating the lack of ethics in socializing. Therefore the authors focus on ethics in teaching, so that Sunday school children can form good character in socializing with others and also improve children's abilities in building ethics given in teaching Christian Religious Education. It is believed that ethical attitudes will play an important role in the character development of Sunday School children, where they will know good things to do in socializing with many people. With ethics it can make it easier to understand Christian Religious Education which is taught to Sunday School children.